DIVERSITAS FLORISTIK DAN STRUKTUR VEGETASI DI HUTAN GUNUNG PAYUNG, TAMAN NASIONAL UJUNG KULON - Purwaningsih Purwaningsih; Tika D. Atikah (BERITA BIOLOGI, 2018)
A floristic diversity and vegetation forest structure was carried out on the Mount Payung, Ujung Kulon National Park. The objective was to floristic composition and structure of the forest located at the peninsula of Ujung Kulon, Banten. The study was conducted using the quadrat method by establishing plots of 5000 m2 each at two locations Pasir Ipis and Gunung Keneng, thus the total area sampled was 1 ha. They were Plot Pasir Ipis and Plot Gunung Keneng. A total of 1898 trees comprising 105 species of 74 genera and 43 families were recorded. The number of species at Pasir Ipis higher (90 species) than plot Gn Keneng (61 species). Based on calculation the important value indexes (IVI), there were some dominan species with IVI >10 at Pasir Ipis Neesia altissima (IV=21,55), Barringtonia racemosa (17,89), Payena acuminata (13,35) and Neonauclea lanceolata (12,37). The dominated species at Plot Gn Kendeng were Pseuduvaria reticulata (IV= 34,30), Dillenia excelsa (27,62), Lagerstroemia speciosa (20,89), Popowia pisocarpa (17,57). The structure of forest could be inferred from the diameter and height of trees. The diameter measurements showed that 75,57 % of trees in plot Pasir Ipis and 80,51 % in plot Gunung Kendeng consist of small individuals with diameters between 10-20 cm. Trees with large diameters of >100 cm occurred in two plots among them Barringtonia racemosa, Polyalthia lateriflora, Popowia pisocarpa, Artocarpus elasticus. The presence of large numbers of small trees and lesser numbers of trees with large diameters in a forest stand indicated that the stand was regenerating after heavy disturbance. The presence of the majority of trees with height of < 20 m (99 %) further confirmed the forest’s dynamic status.